Communication skills training for emergency department senior house officers—a qualitative study. Issue 4 (1st July 2000) - Lloyd, Gavin; Skarratts, Dave; Robinson, Neil; Reid, Cliff
Abstract : Objective —To identify common weaknesses in senior house officer-patient consultation skills, and evaluate direct observation with feedback and negotiation of educational contracts, as a teaching tool in an emergency department setting. Method —Common weaknesses were identified through review of feedback charts by three trained observers. Alteration in clinical and learning behaviour, as well as senior house officer and observer perceptions of the teaching were evaluated qualitatively by a combination of semi-structured interviews and focus groups. Results —Several common weaknesses were identified, notably the use of closed questions, and poor negotiation and explanation of treatment plan and follow up. The senior house officers perceived improvement in their clinical practice, welcomed feedback, and subsequently set, though did not complete educational contracts. While comfortable with this style of teaching, the observers felt that it did not make efficient use of teaching time. Conclusions —This study identifies common weaknesses in the consultation skills of emergency department senior house officers and confirms the need for training in this area. Direct observation is effective in changing behaviour to this end, though self directed learning is not necessarily stimulated. Video recorded consultations with group feedback may be a more effective teaching tool.